The Blackwell Handbook of Mentoring: A Multiple Perspectives Approach - Tammy D. Allen; Lillian Eby (Croydon, England Wiley-Blackwell, 2010)
In recent years, interest in the subject of mentoring and its benefits has increased significantly. But with a plethora of research being conducted in three primary areas (youth, student-faculty, and workplace mentoring) little attention has been paid to the potential advantages of looking across these different types of relationships to provide a more unified and comprehensive understanding of mentoring. Cutting across the fields of psychology, management, education, counseling, social work, and sociology, The Blackwell Handbook of Mentoring reveals an innovative, multidisciplinary approach to the practice and theory of mentoring. In this volume, leading scholars working in each of the three key areas review the critical literatures from their field. Focusing on today's most substantial theoretical approaches and methodological issues, this book combines original theory and landmark research with 20 years of accumulated observations to provide rich and incisive analysis. With a final section that presents an integrated perspective on mentoring relationships and projects a future agenda for the field, this volume is the most complete guide to the subject to date, making it an essential resource for all students, researchers, and related professionals who are looking to stay at the forefront of the discipline.
Keywords: Mentoring; Nonfiction; Leadership and Mentoring (HRM2073-N)